Exchange rates and trade balance adjustment: A multi-country empirical analysis - Michael Bleaney; Mo Tian (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2012)
This study assesses the response of the trade balance to exchange rate fluctuations across a large number of countries. Fixed-effects regressions are estimated for 87 countries on annual data from 1994 to 2010. The trade balance improves significantly after a real depreciation, and to a similar degree, in the long run for all countries, but the adjustment is significantly slower for industrial countries. Emerging markets and developing countries display relatively fast adjustment. Disaggregation into exports and imports shows that the delayed adjustment in industrial countries is almost entirely on the export side. The rate of adjustment in emerging markets is slowing over time, consistent with their eventual graduation to high-income status. The ratio of trade to GDP is also highly sensitive to the real effective exchange rate, with a real depreciation of 10% raising the trade/GDP ratio across the sample by approximately 4%. This result, which presumably reflects movements in the prices of tradables relative to non-tradables, raises questions about the widespread use of the trade/GDP ratio as a trade policy indicator, without adjustment for real exchange rate effects.
Keywords: F14; F41; 330; exchange rate; trade balance; exports; imports; terms of trade